If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6-5n=1-4n
We move all terms to the left:
-6-5n-(1-4n)=0
We add all the numbers together, and all the variables
-5n-(-4n+1)-6=0
We get rid of parentheses
-5n+4n-1-6=0
We add all the numbers together, and all the variables
-1n-7=0
We move all terms containing n to the left, all other terms to the right
-n=7
n=7/-1
n=-7
| −3x/7= 63 | | −3x7= 63 | | 4=k(16)² | | 75x=130 | | 2/3x=89/6 | | 1+6n-3n+1=3n+n | | 1+2a=7 | | -6(h-4)=3(h+9) | | X-(10+10x)=-28 | | 13x+2=17x-2 | | 80°=x+87 | | -10x-5=-8x+10 | | -16=k/8 | | 1/3-t=45 | | 3=p+17 | | 15x-5=70° | | 0.0214=m-0.301 | | –3w−5=–3w−6 | | -8(2-1/48)=2(s-8) | | 1.3b=2.6 | | 20x+5=9x+11 | | –2s=–2s+2 | | 3x-8=4(x+5 | | 8w-28-6w=9w-8-9w | | 16=(2/3)(4)y | | (4y-15)=180 | | b-18=-1 | | -1/10a=-16 | | 2/3x-11=3 | | 7c+4.0=-14.2 | | (2/3)x-11=3 | | 23+4x-39=-11 |